2017
DOI: 10.21276/aimdr.2017.3.5.ot2
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Thickness (CCT) in Diabetic Subjects and its Correlation with Disease Duration and Severity

Abstract: Background: Diabetes mellitus (DM) affects the corneal endothelium by altering the function of Sodium Potassium ATPase activity, thus causing functional changes in diabetic corneas. Associated structural changes if any are important to be recognized timely since it has multiple clinical implications. A few studies have studied corneal morphological changes, including endothelial morphology and corneal thickness in diabetic subjects but it is still a topic of research and there are not many Indian studies in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
1
6
0
3
Order By: Relevance
“…This eventually results in anatomical and functional changes in the cornea. (9) In our study mean CCT was thicker in diabetic groups when compared with the non-diabetics.The difference between the 2 groups was statistically significant (p<0.05)…”
Section: Discussion:-supporting
confidence: 53%
See 2 more Smart Citations
“…This eventually results in anatomical and functional changes in the cornea. (9) In our study mean CCT was thicker in diabetic groups when compared with the non-diabetics.The difference between the 2 groups was statistically significant (p<0.05)…”
Section: Discussion:-supporting
confidence: 53%
“…Diabetes effects cornea by causing corneal endothelial damage and recurrent corneal erosions and persistent epithelial defects. (9) 7. DM affects Na + -K + ATP ase pump, thus causing functional changes in diabetic corneas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dabas R, Sethi S et al found central corneal thickness higher in diabetics with HbA1C>7 (564.44±32.01 μm) in comparison to HbA1C<7 (543.85±23.32μm) (p < 0.009) [12].…”
Section: Original Research Articlementioning
confidence: 94%
“…The hemostasis of various structures of cornea can be altered by the diabetes in both the non-stressed and stressed cornea, causing myriad primary and postoperative manifestations. They have abnormalities like higher corneal autofluorescence, lower corneal sensitivity and lesser endothelial density [4] . Diabetic keratopathy is a frequent disease that entails several alterations, especially in the epithelium and endothelium in diabetics.…”
Section: Introductionmentioning
confidence: 99%